The Egg Coverings of Aak Grasshopper, Poekilocerus Pictus Fabricius (Acridoidea : Pyrgomorphidae) - Parihar, D R (Annals of Arid Zone, 2016)
In the fully developed egg of Poekilocerus pictus the egg-shell is composed of endochorion with outer tubercles, and a thin, structureless vitelline membrane. By the 11-1/2 day stage, the vitelline membrane disappears and the serosa becomes visible. The latter secretes two layers on its outer side a yellow and a white cuticle. At about 23 day stage the white cuticle becomes differentiated into an outer and an inner layer. In the 46 day stage the embryonic cuticle makes its appearance. In the 64 day stage the white cuticle thins greatly. The embryonic cuticle acquires pattern of spine-like papillae, and the hydropyle cellsÂ· become grouped and indistinct.